2023
DOI: 10.3390/molecules28041713
|View full text |Cite
|
Sign up to set email alerts
|

Flavonoid Components, Distribution, and Biological Activities in Taxus: A review

Abstract: Taxus, also known as “gold in plants” because of the famous agents with emphases on Taxol and Docetaxel, is a genus of the family Taxaceae, distributed almost around the world. The plants hold an important place in traditional medicine in China, and its products are used for treating treat dysuria, swelling and pain, diabetes, and irregular menstruation in women. In order to make a further study and better application of Taxus plants for the future, cited references from between 1958 and 2022 were collected fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 91 publications
0
15
0
Order By: Relevance
“…So far, a large number of flavonoids with different skeletons were isolated from Taxus plants. Flavonoids have potential benefits for human health and were reported to be play significant antibacterial, anti-aging, anti-Alzheimer’s, antidiabetic and anticancer . Our data suggest that the leaves of T.…”
Section: Resultsmentioning
confidence: 63%
See 2 more Smart Citations
“…So far, a large number of flavonoids with different skeletons were isolated from Taxus plants. Flavonoids have potential benefits for human health and were reported to be play significant antibacterial, anti-aging, anti-Alzheimer’s, antidiabetic and anticancer . Our data suggest that the leaves of T.…”
Section: Resultsmentioning
confidence: 63%
“…Ascorbic acid, carotenoids, and polyphenols extracted from Taxus baccata red arils exhibit strong antioxidant activities . A number of flavonoids with diverse skeleton structures were reported to exhibit significant antibacterial, antiaging, and antiviral activities . Using the high-performance liquid chromatography with diode-array detection method, several phenolic compounds with antioxidant and anticancer activities were determined in the Taxus cuspidata bark extracts .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to previous studies [ 12 , 13 ], the terpenoids and phenols in volatiles are recognized for their antioxidant and antibacterial components. However, there are some important factors affecting the quality and ingredient composition in terpenoids and phenols, such as the extraction methods used, plants organs, and compounds ingredients etc.…”
Section: Introductionmentioning
confidence: 99%
“…Flavonoid derives from various vegetables and fruits, at least including green tea, citrus fruits, and even onion. Accumulating evidence indicated that flavonoid plays important roles in antivirus and antitumor response and in improving cardiovascular diseases . Recently, emerging studies highlighted that sinensetin (SNS), one of the flavone aglycones, exhibits various bioactivities on anti-inflammation, antioxidant, antitumor antimicrobial, and antiobesity. , SNS served as an inhibitor to target GLUT1 to facilitate sorafenib-induced cytotoxicity of cancer cells, which might contribute to overcoming chemoresistance in cancer treatment .…”
Section: Introductionmentioning
confidence: 99%